Low-Fat Butter: Production and Technological Features - Zakharova L.; Abushahmanova L. (Техника и технология пищевых производств)
Modern lifestyle is characterized by hypodynamy, hypokinesia, overnutrition, and high-calorie products consumption. Hence, food industry has to design low-caloric products. The present paper introduces a new production technology for low-fat butter with dietary fibers. The research featured Bio-fi Pro WR 400 beetroot fiber, namely its sensory, functional, and technological properties, as well as chemical composition. The research objective was to define its further use in low fat butter production. The fiber demonstrated neutral taste, colour, and smell. The sample contained up to 70% of dietary fibers, including 21% of cellulose and 20% of pectin. The research also studied the soaking process of cellulose in distilled water and skim milk at various temperatures. Fat-free milk proved to be the optimal environment, while the optimal temperature for the soaking process was 45 ± 1°C. Temperature experiments proved the samples of dietary fibers to be thermostable. A study of various pasteurization modes and their effect on the sensory properties of cream revealed the following optimal conditions: 95 ± 2°C for 10 minutes. The conditions allowed the samples of high-fat cream to acquire the necessary specific pasteurization taste. In addition, the study featured the effect of dietary fibers on the rheological and sensory properties of low fat butter, as well as its nutrition and energy value. The optimal share of the dietary fiber was determined as 2.5% of the finished product weight. The fat content in the low fat content butter was 1.17 times lower than in the control sample (Krestyanskoe butter brand). Thus, the obtained product demonstrated a low calorific value if compared to traditional butter.